Putting on the Brakes: Regulatory Kinases and Phosphatases Maintaining B Cell Anergy - Franks, S. Elizabeth; Cambier, John C. (Frontiers in Immunology, 2018)
B cell antigen receptor (BCR) signaling is a tightly regulated process governed by both positive and negative mediators/regulators to ensure appropriate responses to exogenous and autologous antigens. Upon naïve B cell recognition of antigen CD79 (the ITAM-containing signaling subunit of the BCR) is phosphorylated and recruits Src and Syk family kinases that then phosphorylate proximal intermediaries linked to downstream activating signaling circuitry. This plasma membrane localized signalosome activates PI3K leading to generation of PIP3 critical for membrane localization and activation of PH domain containing effectors. Conversely, in anergic B cells chronic antigen stimulation drives biased monophosphorylation of CD79 ITAMs leading to recruitment of Lyn, but not Syk, which docks only to bi-phosphorylated ITAMS. In this context, Lyn appears to function primarily as a driver of inhibitory signaling pathways promoting the inhibition of the PI3K pathway by inositol phosphatases, SHIP-1 and PTEN, which hydrolyze PIP3 to PIP2. Lyn may also exert negative regulation of signaling through recruitment of SHP-1, a tyrosine phosphatase that dephosphorylates activating signaling molecules. Alleles of genes that encode or regulate expression of components of this axis, including SHIP-1, SHP-1, Csk/PTPn22 and Lyn, have been shown to confer risk of autoimmunity. This review will discuss functional interplay of components of this pathway and the impact of risk alleles on its function.